Investigation of a jet pump system performance for cleaning of photovoltaics panels - Alsaleh, Sami (2017)
This study is to investigation and development of the PV self -cleaning impacted of dust that would enable a wider deployment of solar photovoltaic systems in the Middle East and Gulf region which enjoys abundant solar radiation throughout the year, and where sandstorm dust and elevated ambient temperature persist. The dust reduces the power generated by the solar devices or hinders the visibility through windshields. The research intends to combine a number of technologies to assist and improve the operational performance of photovoltaic (PV) systems. This investigation covered some of systems which employed PV self-cleaning techniques to remove the particles of dust from the PV panel surface. Regular cleaning of the panels is often necessary to prevent serious degradation of their performance, especially in regions with dusty climates. However, manual cleaning of solar panels, especially in the context of large installation, can be a labour-intensive process and thus often prohibitively costly. Even in small buildings, cleaning a PV system can involve complicated issues of access that might require the intervention of specialist staff. Some of the technologies involve the use of electrodynamic screens for electrostatic dust removal, robotic cleaning tools, vibrating mechanisms featuring piezo-ceramic actuations, as well as TiO2-treated chemical or nano-films. Nevertheless, none of these technologies has to date been able to establish itself as an industry standard and achieve the necessary commercial breakthrough. The numerical and experimental results demonstrate that the diameter of the nozzle throat has a significant impact on the mass flow rate of the water vapour; some results in a high mass flow rate whereas a larger diameter leads to a lower rate. The nozzle diameter also affects the magnitude of the velocity and the mass fraction of the water vapour. It was found that a nozzle throat of a 5 mm diameter above the PV surface by 50 mm with 222m/s is optimum for the jet pump design for water vapour production and dust removal covering sufficient PV surface area. Moreover, variations in the length of the mixing chamber have a significant effect on the mass flow rate of the water vapour. It was found that the mass flow rate of the water vapour is higher in a shorter mixing chamber than it is in a longer mixing chamber. Therefore, to be more effective, a jet pump should have a smaller nozzle diameter, a shorter mixing chamber and a smaller jet pump throat. In light of the above, self-cleaning technologies could present the perfect solution to these issues and help address many of the obstacles preventing solar panel technology from becoming more widely adopted. This would help reduce dependence on the fossil-fuel based energy resources which can be devoted to the generation of national revenues and also leads to a reduction of CO2 emissions to the environment.